Comparison of physical characteristics of mass and luminosity function of disk systems in barred and unbarred spiral galaxies - Al Najm M.N.; Y. E. Rashed; H. H. AL-Dahlaki (مجلة بغداد للعلوم, 2024)
Among the most important ways to investigate galaxies' distribution over cosmic time is the luminosity function LF in terms of baryonic disc mass ψS(Mb), magnitude  . We have studied an estimate of the baryon mass density in the sample of barred and unbarred spiral-type galaxies from previous literature, which virtually involves, for each class of objects with visible baryon content, an integral over the luminosity of the product of the luminosity function (LF) and the mass-to-light ratio. The multiple regression technique used the statistical software package in our study and results, such as database analysis and graphing software (Statistics Win and Origin Pro programs). According to the statistical analysis, there is a strong positive and very relevant correlation (α MB~1), and both barred and unbarred disc spiral galaxies often exhibit MB < -18 mag. The "knee" of the luminosity function for spiral galaxies shows a large cutoff at the baryonic mass of Mb >1010 Mʘ for barred and unbarred spirals. These provide evidence supporting the hypothesis that disc system spirals began to form inside an increased mass threshold. Since the increase of the star's initial mass function with redshift is much more rapid, our findings have indicated that the comoving initial mass function ψS(Mb) of barred and unbarred galaxies at elevated redshift (z > 0.027 for barred and z > 0.02 for unbarred) appears to be declining compared to the critical universe.